Implementasi Kebijakan Mediasi dalam Penyelesaian Masalah Pemutusan Hubungan Kerja (PHK) di Dinas Perindustrian dan Tenaga Kerja Kota Surabaya - Ria Resti Anjani; Indah Prabawati; Tjijik Rahaju; Tauran T (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research is based on the dynamics of the Termination of Employment (PHK) case in Surabaya City which triggered an industrial relations dispute, where the effectiveness of non-litigation mediation at the Surabaya City Industry and Manpower Office is influenced by the level of compliance of the parties. The purpose of the research is to analyze the implementation of industrial relations policies by the Surabaya City Industry and Manpower Office in facilitating dispute resolution and fulfilling the normative rights of workers affected by layoffs. This research method uses a descriptive qualitative approach. Data collection techniques are carried out through interviews, observations, and documentation. Data analysis techniques apply an interactive model including reduction, data presentation, and drawing conclusions. The focus of the research uses the policy implementation theory from Merilee S. Grindle which includes the content of the policy and the context of implementation. The results of the research indicate that the Surabaya City Industry and Manpower Office has carried out its duties and functions well in facilitating dispute resolution, although there are still shortcomings in its implementation. From the aspect of benefit distribution, collective administrative order has been achieved, but the fulfillment of individual rights still faces obstacles due to differences in bargaining positions and limited post-mediation supervision. Research suggestions include the need to increase the number of functional mediators, transparency, and strengthening regulations.